Synthesis and photovoltaic properties of two new alkoxylphenyl substituted thieno[2, 3-f]benzofuran based polymers1. Issue 27 (21st July 2015) - Qiu, Beibei; Cui, Ruili; Yuan, Jun; Peng, Hongjian; Zhang, Zhiguo; Li, Yongfang; Zou, Yingping
<x xml:space="preserve">Abstract</x> Two alkoxylphenyl substituted thieno[2, 3-f]benzofuran (TBFP)-based polymers (PTBFP–BT and PTBFP–BO) were synthesized. The PSCs based on PTBFP–BT : PC71BM (1 : 2, w/w) exhibited a promising PCE of 6% with a high FF of 0.69.